2013
DOI: 10.4161/mabs.24981
|View full text |Cite
|
Sign up to set email alerts
|

Analytical FcRn affinity chromatography for functional characterization of monoclonal antibodies

Abstract: The neonatal Fc receptor (FcRn) is important for the metabolic fate of IgG antibodies in vivo. Analysis of the interaction between FcRn and IgG in vitro might provide insight into the structural and functional integrity of therapeutic IgG that may affect pharmacokinetics (PK) in vivo. We developed a standardized pH gradient FcRn affinity liquid chromatography method with conditions closely resembling the physiological mechanism of interaction between IgG and FcRn. This method allows the separation of molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
144
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(156 citation statements)
references
References 39 publications
5
144
0
Order By: Relevance
“…The effects in the Ab wt Fab upon FcRn binding were reproducible and were observed in replicate HDX-MS experiments (n ϭ 3). This result provides strong experimental evidence of a conformational origin in line with earlier biochemical studies that indicate a role of IgG Fab in FcRn binding (34,50,51). The sequence of the antibody used in this study (Ab wt ) has standard human constant regions (hIgHG1 and light chain), and a comparison of V region sequences of Ab wt with the closest human germlines showed that the V and J elements has 90% identity with the closest human germline (data not shown).…”
Section: Impact Of Antibody Deglycosylation On Conformation Andsupporting
confidence: 88%
See 3 more Smart Citations
“…The effects in the Ab wt Fab upon FcRn binding were reproducible and were observed in replicate HDX-MS experiments (n ϭ 3). This result provides strong experimental evidence of a conformational origin in line with earlier biochemical studies that indicate a role of IgG Fab in FcRn binding (34,50,51). The sequence of the antibody used in this study (Ab wt ) has standard human constant regions (hIgHG1 and light chain), and a comparison of V region sequences of Ab wt with the closest human germlines showed that the V and J elements has 90% identity with the closest human germline (data not shown).…”
Section: Impact Of Antibody Deglycosylation On Conformation Andsupporting
confidence: 88%
“…Recombinant human FcRn expressed in HEK293F cells was purified as described previously (34) and buffered in 50 mM Na phosphate, 50 mM NaCl, pH 6.5 (Roche Diagnostics). All other chemicals were of the highest grade commercially available.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…37 No negative control experiment was reported determining retention time on an uncoated column to gauge the contribution of nonspecific interactions with the streptavidin sepharose itself (e.g., as reported here in Fig. 2D).…”
Section: Discussionmentioning
confidence: 99%